The importance of being [insert preferred name here]: academic naming conventions with particular reference to Malaysia - Dent, Michael M * (Academia Industry Networks, 2020)
In any cross-cultural communication getting someone’s name wrong is a constant source of worry and potential embarrassment. More importantly the naming styles and conventions of many countries creates confusion, Malaysia being ‘Truly Asia’ suffers from this particularly due to it having three major different ethnic groups (Malay’s, Malaysian Chinese and Malaysian Indians) within the population. This paper is based on inductive research living in Malaysia over the past fifteen years. As University rankings drive an increased number of international academic appointments this creates a problem with referencing and citations. Failure to follow a standardised notation may result in publications being omitted from an Academic’s profile –be it under Research Gate or Google Scholar. Consequently, an early decision on one’s preferred academic name is required. Whichever name is chosen, it must be promulgated consistently on every piece of marketing collateral that the institution or individual publishes.